Revitalisasi Manajemen Perpustakaan Perguruan Tinggi dalam Menstimulasi Minat Baca: Evaluasi Berbasis Model CIPP - Muh Rizal; Dahlia (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
The low level of reading interest among Indonesian students, which UNESCO data reports at a mere 0.001%, significantly impacts the quality of human resources and academic productivity. This phenomenon is reflected in the drastic decline of library visits within higher education environments. This study aims to evaluate library management in enhancing student reading interest by implementing the CIPP (Context, Input, Process, Product) evaluation model. Utilizing a qualitative approach, data were collected through in-depth interviews, observations, and documentation involving the head of the library, the Quality Assurance Institute (LPM), lecturers, and students as key informants. The results of the context evaluation indicate low student reading motivation and limited institutional financial support. The input evaluation reveals that the literature collection and physical facilities have not met ideal standards, alongside the absence of standardized operating procedures (SOPs). Regarding the process aspect, although librarian services are considered adequate, their effectiveness is hindered by low student compliance with regulations. Finally, the product evaluation confirms that current management outputs have not yet optimized library visitation rates, which correlates directly with low reading interest. This study recommends updating collections based on user needs, developing creative literacy programs, and intensifying service promotion through social media. The implementation of these strategic steps is expected to reposition the library as a dynamic learning center to support sustainable student academic success.